Uric acid is an independent predictor of cardiovascular events in post-menopausal women. (15th October 2015) - Sciacqua, Angela; Perticone, Maria; Tassone, Eliezer J.; Cimellaro, Antonio; Miceli, Sofia; Maio, Raffaele; Sesti, Giorgio; Perticone, Francesco
Abstract: Background: Uric acid (UA) is a risk factor for cardiovascular (CV) disease. In post-menopause UA levels are increased and strongly associated with subclinical organ damage. We investigated the prognostic significance of UA levels in predicting CV morbidity and mortality in post-menopausal women. Methods: We considered 645 post-menopausal outpatients not taking hormone replacement therapy or any drugs interfering with UA levels. We evaluated major adverse cardiovascular events (MACE) as primary endpoint, with coronary, stroke or total events as secondary endpoint. Survival curves for tertiles of UA were obtained by using the Kaplan–Meier and Mantel methods. Effect of prognostic factors on survival was evaluated by multivariable Cox regression model, considering P < 0.05 as statistically significant. Results: During a mean (SD) follow-up at 72.5 (23.5) months, there were 90 new CV events (2.31%): 62 coronary and 28 cerebrovascular events. The rate of nonfatal CV events (3.15% versus 2.03% and 1.52%, P = 0.009) as well as that of MACE (3.23% versus 2.11% and 1.59%, P = 0.011) were significantly higher in the third tertile than in the other two groups. Interestingly, cerebrovascular (1.15% versus 0.62% and 0.30%, P = 0.027) but not coronary events were significantly different among the three groups. In the Cox regression model, UA was independently and strongly associated with the incident risk of MACE (HR = 1.248, P = 0.001), cerebrovascular (HR = 1.657, P < 0.0001) and total events (HR = 1.391, P < 0.0001). Conclusions: In post-menopause, independently of other CV risk factors and menopause duration, UA levels are associated with increased risk of death and MACE, in particular cerebrovascular but not coronary events.